Intervention effects of telenursing based on M-O-A model in empty-nest older adult individuals with chronic diseases: a randomized controlled trial - Yuan, Yuan; Hou, Ping; Wang, Sican; Kitayama, Akio; Yanagihara, Kiyoko; Liang, Jingyan (Frontiers in Public Health, 2024)
Aim: This study aims to verify the effectiveness of M-O-A telenursing intervention model in improving the health status and quality of life of the empty-nest elderly individuals with chronic diseases by a randomized comparative trial.Methods: M-O-A telenursing intervention model was constructed based on the needs of the participants. The control group (N=39) received routine nursing, the experimental group (N=39) received M-O-A telenursing intervention in addition to routine nursing. After 12 weeks of intervention, the intervention effects of being a participant in the two groups were evaluated. SPSS 26.0 was used for data analysis.Results: After 12 weeks of intervention, for the experimental group, each dimension of quality of life based on EQ-5D-3L became better, especially for "pain/discomfort", "anxiety/depression", "HRQoL" and "EQ-VAS" (all P<0.05) and each dimension of quality of life based on SF-36 became better too, especially for "GH", "BP", "RE", "MH", "VT", "SF", "PCS", "MCS", "SF-36" (all P<0.05). In addition, there was a statistical downward trend in blood pressure, blood glucose, weight, BMI, fat rate, nap duration, number of nocturnal awakenings, light sleep rate and a statistical upward trend in water rate, basal metabolic rate, nighttime sleep duration, deep sleep rate, rapid eye movement sleep rate, especially at the end of intervention (all P<0.05).While for the control group, there was no statistical improvement in all these aspects.The M-O-A telenursing model could effectively regulate quality of life and health condition of the empty-nest elderly individuals with chronic diseases, making it worthy of further promotion and application.